Primary Leiomyosarcoma of the Kidney: A Case Report - Srijana Khati; Sagar Rana Magar; Ankita Simkhada; Ramesh Paudel; Surendra Khanal; Bishal Panthi; Sadmarg Thakur; Sujan Paudel; Prajjwol Luitel (Clinical Case Reports)
ABSTRACT Primary renal leiomyosarcoma is a rare but highly aggressive tumor with a poor prognosis. Early detection and surgical excision provide the most effective initial treatment. However, vigilant postoperative surveillance is critical due to the elevated risk of tumor recurrence and metastasis, as seen in this case.